2010
DOI: 10.1007/s00018-010-0568-3
|View full text |Cite
|
Sign up to set email alerts
|

Viperin mRNA is a novel target for the human RNase MRP/RNase P endoribonuclease

Abstract: RNase MRP is a conserved endoribonuclease, in humans consisting of a 267-nucleotide RNA associated with 7–10 proteins. Mutations in its RNA component lead to several autosomal recessive skeletal dysplasias, including cartilage-hair hypoplasia (CHH). Because the known substrates of mammalian RNase MRP, pre-ribosomal RNA, and RNA involved in mitochondrial DNA replication are not likely involved in CHH, we analyzed the effects of RNase MRP (and the structurally related RNase P) depletion on mRNAs using DNA microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Many siRNA and DNA gapmer/antisense oligonucleotide (ASO) reagents failed to affect steady-state MRP RNA abundance, consistent with previous reports (Mattijssen et al 2011). In our hands, only a single siRNA sequence targeting nucleotides 135-154 of MRP RNA achieved modest depletion of MRP RNA by quantitative RT-PCR (qRT-PCR) and RNA fluorescent in situ hybridization (FISH) (Supplemental Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Many siRNA and DNA gapmer/antisense oligonucleotide (ASO) reagents failed to affect steady-state MRP RNA abundance, consistent with previous reports (Mattijssen et al 2011). In our hands, only a single siRNA sequence targeting nucleotides 135-154 of MRP RNA achieved modest depletion of MRP RNA by quantitative RT-PCR (qRT-PCR) and RNA fluorescent in situ hybridization (FISH) (Supplemental Fig.…”
Section: Resultssupporting
confidence: 89%
“…(We use the term "MRP/P" to indicate the mixture of these two RNPs, which copurify because of their shared protein components.) Others (Welting et al 2006;Mattijssen et al 2011) have shown that N-terminal tags on MRP/P protein components enable immunopurification of pre-tRNA cleavage activity from human cells. Building on these observations and in response to ineffective isolation of RNase MRP via tagging the MRP RNA (data not shown), we constructed 3xFlag-Rpp25 and 3xFlag-Rpp38 for transfection in HeLa cells (see the Supplemental Material).…”
Section: Immunopurified Human Mrp Rnp Specifically Cleaves Fragments mentioning
confidence: 99%
See 1 more Smart Citation
“…Pop1 mutations affect the holoenzyme assembly and result in destabilization of the RNA component in the cell as well as in substrate processing defects in both RNase P and RNase MRP (Lygerou et al 1994;Chamberlain et al 1998;Xiao et al 2006). In humans, certain Pop1 mutations result in a severe skeletal dysplasia (Glazov et al 2011), similar to the dysplasias caused by mutations in the RNase MRP RNA or by defects in RNase MRP RNA promoter region (Ridanpaa et al 2001;Mattijssen et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that viperin was a target of human RNase endoribonuclease (33) and that UL41 was an endoribonuclease with a substrate specificity similar to that of RNase A (26). Therefore, it is very likely that UL41 abolishes viperin expression via its RNase activity to degrade viperin mRNA.…”
mentioning
confidence: 99%